From famine to fulfilment - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
The famines which devastated Ethiopia a decade ago are hopefully a thing of the past, as the country has turned itself around from importer to exporter of grain. A combination of the effects of market liberalization and a period of good rains has...